The effectiveness of avocado (Persea americana M.) leaves infusion as urinary stones dissolving in rats - Ni Made Dwi Sandhiutami; Rika Sari Dewi; Alya Fariha (Pharmaciana, 2022)
Urolithiasis is a pathological condition marked by the formation of urinary stones (calculi) in the urinary tract. Avocado leaf (Persea americana M.) contains substances that play crucial roles in the solubility of calcium in urinary stones, such as flavonoids, alkaloids, saponins, and magnesium. Empirically, avocado leaves are used to make urinating easier and break stones in the urinary tract. This study aims to determine the effect of avocado leaf infusion to dissolve urinary stones in white male rats. According to the experiment, 24 male white rats were divided into four groups; the negative control group (not given infusion), the 1 g/kg BW dose group, the 2 g/kg BW dose group, and the 3 g/kg BW dose group of avocado leaves infusion. The infusion was administered orally for seven consecutive days after 28 days of planting black silk thread as the stone core in the urinary tract. Then, the stone formed is taken. The weight and volume are measured. The urinary stones were tested qualitatively in terms of calcium and oxalate. The results showed that there were significant differences among treatment groups in weight and volume of urinary stones. The effect of bladder stone dissolving was best in the 3 g/kg BW group. The qualitative test also shows that urinary stones contain the same calcium and oxalate as urinary stones that form in humans. Avocado leaves infusion can have a urinary stone dissolving effect on white male rats. Increasing the dose of avocado leaves infusion increases its effectiveness as a urinary stone dissolution.